Development And Utilisation Of Urban Open Spaces In Islamabad - JAVAID, BEENISH; WAHEED, ABDUL (The journal of contemporary issues in business and government, 2021)
This research work explores the onsite condition of Urban Open Space in the city of Islamabad. Urban Open Spaces play a significant role in the development of a city. These spaces also determine the outlook of the city. The impact of these spaces on the residents/community is immense. Therefore, the Urban Open Spaces should be planned to ensure the safety and satisfaction of the public. These places are used for plantation, landscaping, and decoration of a city and when left unplanned, these can encourage criminal activities. This study explores whether these spaces are planned and developed according to the planning parameters prevailing worldwideThese, in turn, help define the efficiency of parks and open spaces in terms of the requirements of Islamabad citizens. For this purpose, the Urban Open Spaces of two residential sectors were selected. The research concludes that the elements of Urban Open Spaces in two residential sectors require detailed treatment. Currently, city management is not emphasising the importance of planning, preserving, and managing Urban Open Spaces in the residential sectors of Islamabad.